Electron transfer induced by collision of low-energy doubly charged carbon ions with tetrahydrofuran. (July 2015) - Erdmann, Ewa; Łabuda, Marta
Synopsis: In this communication, we present results of recent investigations of charge transfer process in the collision of C 2+ ions with heterocyclic molecule of tetrahydrofuran.